2020
DOI: 10.3390/en14010025
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Approach to Evaluate the Effect of Reducing District Heating Temperature on Indoor Thermal Comfort

Abstract: To reduce energy consumption for space heating, a coordinated action on energy supply, building fabric and occupant behavior is required to realize sustainable improvements. A reduction in district heating supply temperature is an interesting option to allow the incorporation of renewable energy sources and reduce distribution losses, but its impact on the final users must be considered. This aspect is especially critical as most European countries feature an old building stock, with poor insulation and heatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
0
11
0
3
Order By: Relevance
“…The EN-ISO 7730 standard uses the thermal comfort model of Fanger [30,[95][96][97][98][99] assuming that people feel comfortable when the internal heat production in the body is equal to the loss of heat to the environment. Solution of this thermal balance at given thermal and environmental conditions results in calculation of two empirical comfort indexes.…”
Section: Pmv and Ppdmentioning
confidence: 99%
“…The EN-ISO 7730 standard uses the thermal comfort model of Fanger [30,[95][96][97][98][99] assuming that people feel comfortable when the internal heat production in the body is equal to the loss of heat to the environment. Solution of this thermal balance at given thermal and environmental conditions results in calculation of two empirical comfort indexes.…”
Section: Pmv and Ppdmentioning
confidence: 99%
“…Vaisi et al [9] provided a new thermal energy benchmark for university buildings focusing on monthly resolution in order to improve the accuracy of national action plans and their realization for energy-efficient built environment. In the tenth paper, Grassi et al [10] investigate how the reduced temperature of a secondgeneration district heating supply can be handled despite the possible occurrence of discomfort caused by the lower output of radiators when working at reduced temperatures. In [11], Cumo et al present a decision support tool for selecting the best energy retrofitting strategies integrated with a GIS tool for helping planners and Public Administrators.…”
Section: Overview Of the Articles In This Special Issuementioning
confidence: 99%
“…The waste heat may be utilized more effectively in 5DE districts. Grassi, P. et al have investigated the potential impact of low supply temperatures on the indoor human thermal comfort sensation [33]. Their simulations for different building typologies in Italy showed that the most severe discomfort situations are experienced in buildings built before 1990.…”
Section: Low-temperature District Energy Systemsmentioning
confidence: 99%